2019
DOI: 10.18597/rcog.3357
|View full text |Cite
|
Sign up to set email alerts
|

Manejo conservador en una paciente con embarazo ectópico cervical en Nariño, Colombia: reporte de caso y revisión de la literatura

Abstract: RESUMENObjetivos: reportar el caso de un embarazo cervical (EC) que recibió manejo conservador exitoso y realizar una revisión de la literatura sobre el tratamiento médico y quirúrgico conservador. Materiales y métodos: se presenta el caso de una paciente con embarazo cervical, quien recibió manejo farmacológico con metotrexate (MTX) y posterior legrado con evolución clínica satisfactoria. Se realizó una búsqueda de artículos en Medline vía PubMed, LILACS, SciElo y Google académico con los términos: "cervical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Persadie et al reported the administration of multiple doses of methotrexate followed by removal with forceps and curettage, a therapeutic method that resulted in septicemia caused by E. Coli [ 24 ]. Bolaños-Bravo et al mentioned a more sophisticated approach in which they combined the systematic administration of methotrexate followed by dilation and curettage, and subsequently the placement of a Foley catheter, to prevent any potential urgent hemorrhage [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Persadie et al reported the administration of multiple doses of methotrexate followed by removal with forceps and curettage, a therapeutic method that resulted in septicemia caused by E. Coli [ 24 ]. Bolaños-Bravo et al mentioned a more sophisticated approach in which they combined the systematic administration of methotrexate followed by dilation and curettage, and subsequently the placement of a Foley catheter, to prevent any potential urgent hemorrhage [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ultrasound criteria to establish the diagnosis consists of the 1) absence of an intrauterine pregnancy, 2) presence of a gestational sac below the level of the internal cervical os, 3) absence of a sliding sign, and 4) presence of flowing blood around the gestational sac detected by Doppler [6]. Other additional signs include closed internal cervical os, an "8" or hourglass uterine shape (because of the ballooned cervical canal), endometrial decidualization, and the presence of embryonic structures in the ectopic gestational sac [7]. Regarding ultrasound features, cervical pregnancy can easily be misdiagnosed as scar pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, combined therapy with intra-amniotic methotrexate may increase the effectiveness of the treatment. In the presence of a heartbeat, an intraamniotic administration of potassium chloride for embryocide or feticide is also recommended [7]. Some authors describe beneficial effects in aspiration and injection of approximately equal amounts of volume into the cavity when performing the intra-amniotic injection, so the internal pressure does not vary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation